Physicians' Practice, Attitudes Toward, and Knowledge of Cancer Pain Management in China. Issue 11 (27th June 2015) - Zhang, Qiongwen; Yu, Chunhua; Feng, Shijian; Yao, Wenxiu; Shi, Huashan; Zhao, Yuwei; Wang, Yongsheng
Abstract: Subject: To evaluate physicians' current practice, attitudes toward, and knowledge of cancer pain management in China. Methods: We conducted a face‐to‐face survey of physicians (oncologists, internists, hematologists) who are responsible for the care of cancer patient of 11 general hospitals in Sichuan, China between December 2011 and December 2013. Statistical analyses were performed using SPSS (SPSS, Chicago, IL) software. Setting and Design: A 23‐item questionnaire was designed and distributed to 550 physicians in 11 medical facilities in China. Results: Five hundred (90.90%) physicians responded. About one‐third (32.6%) of physicians assessed patients' pain rarely, and 85.5% never or occasionally treated patients' cancer pain together with psychologists. More than half of physicians indicated that opioid dose titration in patients with poor pain control and assessment of the cause and severity of pain were urgently needed knowledge for cancer pain management. Inadequate assessment of pain and pain management (63.0%), patients' reluctance to take opioids (62.2%), and inadequate staff knowledge of pain management (61.4%) were the three most frequently cited barriers to physicians' pain management. Conclusions: Physicians' positive attitudes toward cancer pain management need to be encouraged, and active professional analgesic education programs are needed to improve pain management in China.